Integrating Digital Transformation, Internal Control, and Socio-Spiritual Values for Sustainable Competitive Performance of MSMEs - Eskasari Putri; Abid Ramadhan; Ashar Mukhammad Akbar; Mochammad Adhitya Wibawa; Rosa Indah Febriyanti; Aisyah Laras Prahastiwi (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Despite extensive research on internal control, digital transformation, and socio-spiritual values, their integrated impact on the sustainable competitive performance of MSMEs remains underexplored, particularly in developing economies. This study aims to analyze the combined effects of internal control components, digital transformation, and socio-spiritual values on MSME performance in Indonesia. A quantitative approach was employed using a cross-sectional survey of 416 MSME actors in Central Java province, selected through purposive sampling. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that all internal control elements, digital transformation, and socio-spiritual values have a positive and significant effect on sustainable competitive performance, with digital transformation emerging as the most influential factor, followed by monitoring activities and socio-spiritual values. These results point out the importance of integrating technological capability, effective governance, and value-based practices in strengthening MSME sustainability. The study extends the Resource-Based View and internal control framework by incorporating socio-spiritual values as strategic resources and offers practical guidance for developing adaptive and sustainable MSME strategies.